Digest: Evolution of mutual ornamentation in hummingbirds. (1st March 2020) - Robert, Aloïs
Abstract: Why are female birds ornamented? In a comparative phylogenetic study of hummingbirds ( Trochilidae ), Clark and Rankin tackled this crucial question and investigated how male tail evolution is reflected in female morphology.